Static Balance in Older Adults With Chronic Obstructive Pulmonary Disease Undergoing Pulmonary Rehabilitation - Clara Narcisa Silva Almeida; Rayane Alves da Costa; Kaio Primo Manso; Juliana Figueiredo Ferreira; Bianca Callegari; Cristino Carneiro Oliveira; Laura Maria Tomazi Neves (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: To compare balance between older adults with and without chronic obstructive pulmonary disease (COPD) in tasks involving proprioceptive changes and respiratory muscle load, and to investigate the association between balance, functional capacity, and peripheral and respiratory muscle strength. METHODS: Fourteen older adults with COPD undergoing pulmonary rehabilitation and nine older adults without pulmonary disease were evaluated for static balance on a force platform under four conditions: eyes open, eyes closed, eyes closed on foam, and eyes open with respiratory overload. Differences between groups, among conditions and group/condition interactions, were tested using two-way ANOVA. Associations were explored using Pearson's correlation coefficient. RESULTS: No differences in the posturographic variables were found in the group/condition interactions (p ≥ 0.23). The COPD group exhibited greater total displacement (F = 8.79, p = 0.003), mediolateral sway (F = 4.01, p = 0.04) and anteroposterior velocity (F = 4.28, p = 0.04) in the group effect analysis. Significant differences were found between eyes closed on foam and other conditions for all posturographic variables: anteroposterior sway (F = 13.39), mediolateral sway (F = 28.58), total displacement (F = 59.4), area (F = 37.68), anteroposterior velocity (F = 26.42), and mediolateral velocity (F = 33.29), in the condition effect analysis (p < 0.001, post-hoc). In the COPD group, significant correlations were found between the Glittre-ADL test, anteroposterior sway (r = 0.68, p = 0.01), and anteroposterior velocity (r = 0.67, p = 0.009); the 6MWT was also correlated with anteroposterior velocity (r = 0.59, p = 0.03). CONCLUSION: Older adults with COPD present balance deficits compared to healthy individuals. The unstable surface caused greater postural instability compared to other conditions in both groups. Impaired balance was associated with reduced physical function and exercise capacity.